Percentage of apparent sucrose and productive potential of sugar in cane cultivars - Da Silva Neto, Hélio Francisco (2014)
The percentage of saccharose apparent "POL" is an important variable for the determination of sugar production, and its value differs among the cultivars, plant parts and growth seasons. The study aimed to compare values of POL and estimate productive potential of sugar in juice extracted from nodes and internodes of the sugarcane cultivars sugar during the 2010/2011 crop season. We used the experimental design of randomized blocks in factorial scheme 3x2x6, with four replications. The main treatments were cultivars of sugarcane, the secondary treatments two parts of the stalks of sugarcane, and third the seasons of analysis distributed over the harvest. The cultivars RB72454 and SP81-3250 showed the highest values POL. Conversely, the RB867515 obtained less satisfactory results, showing lower value of POL throughout the study period, and the two parts of the stalk. The internode was greater than POL, and showed greater potential for sugar production when compared to the stalk portion represented by the node. The values of POL and the productive potential of sugar, obtained by both sides of the stalk were growing throughout the season, and coincided with the harvest season recommended for these cultivars. However, there was this period that the biggest difference between the parts of the stalk, indicating the need for a better use of the internode